PENENTUAN GOLONGAN SEYAWA DAN TOTAL FLAVONOID EKSTRAK ETANOL SARANG SEMUT (Myrmecodia pendens Merr & Perry) SECARA SPEKTROFOTOMETRI UV-VIS - Susilowati; Estiningrum, Dian (Jurnal Farmasi (Journal of Pharmacy), 2016)
Myrmecodia pendens Merr.& Perry. is a plant that has been widely used as a traditional medicine. One of the chemical active componen in Myrmecodia pendens is flavonoid . The purpose of this study was to determine flavonoid group and that content in Myrmecodia pendens. Extraction method used maceration with 96% ethanol. Qualitative test conducted by phytochemical screening and TLC with stationary phase silica GF254nm and buthanol:acetic acid: water ( 4:1:5 ) as mobile phase. Flavonoid group dan quanitative assay used UV- Vis spectrophotometry methode. The results showed that in Myrmecodia pendens extract contains flavonoids kind Flavonols 3-OH-free and 5-OH-free. Flavonoid total of Myrmecodia pendens ethanol extract 0,6126 % b ⁄b of quercetine.